1998
DOI: 10.1097/00000374-199802000-00036
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol Tolerance and Withdrawal Responses in GABAAReceptor Alpha 6 Subunit Null Allele Mice and in Inbred C57BL/6J and Strain 129/SvJ Mice

Abstract: We have been using a genetic strategy to define the contribution of specific candidate genes, such as those encoding subunits of the gamma-aminobutyric acid type A receptor, to various ethanol sensitive responses. We have used the gene knockout approach in mouse embryonic stem cells to create mice in which the gene encoding the alpha6 subunit of the gamma-aminobutyric acid type A receptor is rendered nonfunctional. In the present report, we provide a detailed characterization of several behavioral responses to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 0 publications
3
10
0
Order By: Relevance
“…Exposure to air + pyrazole produced a slight enhancement of HIC within the early phase of withdrawal (i.e., 1 st 12 hrs), which subsequently decreased to baseline levels. This finding is consistent with the report by Homanics et al (1998) in which control 129/SvJ mice exhibited marked HIC that peaked approximately 2–3 hr post-removal from the inhalation chamber and returned to baseline at 8 hr. Thus, all of our experiments employed the use of pyrazole in the air controls to offset any potential confound due to a small proconvulsant effect of pyrazole in some genotypes.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Exposure to air + pyrazole produced a slight enhancement of HIC within the early phase of withdrawal (i.e., 1 st 12 hrs), which subsequently decreased to baseline levels. This finding is consistent with the report by Homanics et al (1998) in which control 129/SvJ mice exhibited marked HIC that peaked approximately 2–3 hr post-removal from the inhalation chamber and returned to baseline at 8 hr. Thus, all of our experiments employed the use of pyrazole in the air controls to offset any potential confound due to a small proconvulsant effect of pyrazole in some genotypes.…”
Section: Resultssupporting
confidence: 92%
“…Since the WT mice are a hybrid of C57BL/6J and 129/SvJ background strains, we were unsure whether ethanol withdrawal in this genotype would be mild (similar to C57BL/6J) or moderate to severe (similar to 129/SvJ) and whether the air-controls would exhibit mild HICs as has been reported for 129/SvJ genotypes (Homanics et al, 1998; Metten and Crabbe, 2005). The pattern of hourly HIC scores in the ethanol- and air-exposed mice in the present study (Figure 6A & 6B) was comparable to that in the 129/SvJ male mice (Homanics et al, 1998; Metten and Crabbe, 2005), consistent with the contribution of genes from 129/SvJ strains to the HIC phenotype in the KO and WT mice.…”
Section: Discussionmentioning
confidence: 99%
“…When the null mutants from this same N6 generation were outcrossed to 129/SvEvTac mice, tolerance to the hypothermic, but not the sedative-hypnotic, effects of ethanol was exhibited by the null mutant mice. These results serve to substantiate the relevance of including the effects of genetic background when evaluating the effects of single gene mutations on complex behavioral phenotypes (Gerlai, 1996;Wehner and Bowers, 1995;Banbury Conference, 1997;Homanics et a]., 1998). In addition, initial sensitivity to the hypothermia-inducing effects of ethanol was not decreased in these populations.…”
Section: Discussionmentioning
confidence: 65%
“…In their study, the phenotype of the parental 129/SvEvTac inbred strain was virtually identical to the D2 receptor-deficient mice, suggesting that cosegregation of 129 alleles around the D2 allele were responsible for the locomotor impairments in the null mutant mice. In studies of ethanol-induced sedation, tolerance, and withdrawal responses in GABA, receptor a6 null mutant mice, Homanics et al (1997Homanics et al ( , 1998 also reported that the background alleles from the parental strains, C57BWGJ and 129/SvJ, appeared to mediate the lack of ethanol responses in the null mutant mice. However, the explanation of differences in ethanol tolerance observed in the present study is more complicated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation